2002
DOI: 10.1074/jbc.m202856200
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Separation of Vesicle Release from Vesicle Fusion during Exocytosis

Abstract: During exocytosis, vesicles in secretory cells fuse with the cellular membrane and release their contents in a Ca 2؉ -dependent process. Release occurs initially through a fusion pore, and its rate is limited by the dissociation of the matrix-associated contents. To determine whether this dissociation is promoted by osmotic forces, we have examined the effects of elevated osmotic pressure on release and extrusion from vesicles at mast and chromaffin cells. The identity of the molecules released and the time co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 49 publications
5
58
2
Order By: Relevance
“…4 and 8). The likely explanation is that, under hypertonic conditions known to inhibit endocytosis (37)(38)(39)(40), components of exocytosed vesicles can migrate laterally in the plasma membrane (e.g. Ref.…”
Section: Discussionmentioning
confidence: 99%
“…4 and 8). The likely explanation is that, under hypertonic conditions known to inhibit endocytosis (37)(38)(39)(40), components of exocytosed vesicles can migrate laterally in the plasma membrane (e.g. Ref.…”
Section: Discussionmentioning
confidence: 99%
“…1Diii). This might reflect a form of kiss-and-run or 'kiss-and-hold' (Troyer and Wightman, 2002), in which exocytosis reversed or arrested after formation of a fusion pore. Alternatively the acrosomal matrix of these few cells might be effectively insoluble.…”
Section: Temporal and Spatial Characteristics Of The Acrosome Reactionmentioning
confidence: 99%
“…The formation of this pore is a complex event involving physical and chemical factors and is regulated by intracellular Ca 2ϩ and proteins (7). Studies on mast cells and chromaffin cells revealed that the opening of fusion pore and extrusion of granule content is influenced by an osmotic force depending upon the osmolarity of the surrounding solution (8).…”
mentioning
confidence: 99%